PERANCANGAN MEDIA PEMBELAJARAN MOBILE APPS BERBASIS ANDROID B’TRACE MERANGKAI GERAK TARI TRADISIONAL - Samsul Fajri; Fuja Siti Fujiawati; Alis Triena Permanasari (JPKS (Jurnal Pendidikan dan Kajian Seni), 2021)
Abstract : Technological developments are increasingly moving rapidly which results in significant changes in human life, one of which is the presence of smartphones. Smartphones are one of the tools that can facilitate the process of disseminating information, communicating and other activities, this need is clear evidence of developments in the present. The increasing use of smartphones ultimately affects people's needs for mobile applications that can make it easier for people to carry out their daily activities. It can be seen from the many applications that can help the needs and interests of the community, for example online shopping, communication with colleagues, directions, playing games, online payments, and online learning. Researchers are finally interested in conducting research on the design of learning applications for Android-based mobile apps on the subject of art and culture, the material of arranging traditional dance movements for grade VIII junior high school students. The purpose of this research is to determine the process of designing and testing the feasibility of learning media based on android. The research method used is research and development (R&D) with the ADDIE development model (analysis, design, development, implementation, evaluation). Based on several assessments of media experts, materials, and users related to learning media, the percentage level of media experts is 84.2% for the category of “very feasible” to use, 94.7% for material experts in the “very feasible” category to use, and 78.2% for users in the “very feasible” category to use. Keywords: Media design for learning, Media for learning, Mobile Apps, Traditional dance movement  Abstrak : Perkembangan teknologi yang semakin hari semakin bergerak pesat yang mengakibatkan adanya perubahan yang signifikan dalam kehidupan manusia salah satunya dengan adanya smartphone. Smartphone merupakan salah satu alat yang dapat mempermudah dalam proses penyebarluasan informasi, berkomunikasi, dan aktivitas lainnya, kebutuhan ini merupakan bukti nyata adanya perkembangan dimasa sekarang ini. Meningktanya penggunaan smartphone yang akhirnya mempengaruhi kebutuhan masyarakat akan aplikasi mobile yang dapat mempermudah masyarakat dalam menjalankan aktivitas sehari-harinya. Dapat dilihat dari banyaknya aplikasi yang dapat membantu kebutuhan dan kepentingan masyarakat, misalnya belanja online, komunikasi dengan rekan kerja, petunjuk arah, bermain game, pembayaran online, dan pembelajaran online. Peneliti akhirnya tertarik untuk melakukan penelitian tentang perancangan aplikasi pembelajaran mobile apps berbasis android pada mata pelajaran seni budaya materi merangkai gerak tari tradisional untuk SMP kelas VIII. Tujuan dalam penelitian ini yaitu untuk mengetahui proses perancangan dan uji kelayakan media pembelajaran berbasis android. Metode penelitian yang digunakan adalah reseach and development (R&D) dengan model pengembangan ADDIE (analysis, desain, development, implementation, evaluation). Berdasarkan beberapa penilaian ahli media, materi, dan pengguna terkait media pembelajaran dengan tingkat persentase ahli media 84.2% kategori “sangat layak” digunakan, ahli materi 94.7% kategori “sangat layak” digunakan, dan pengguna 78.2% kategori “sangat layak” digunakan. Kata kunci: Perancangan Media pembelajaran, Media Pembelajaran, aplikasi mobile, Gerak Tari Tradisional